Construction and function validation of inducible immortalized gene integration vectors - YUE Wei; YANG Yue; QIAN Baohua; LI Yanxin; GU Haihui (Zhongguo shuxue zazhi)
[Objective] To construct inducible immortalization gene vectors for transfection into primary cells, enabling the establishment of a conditionally immortalized cell line that support their sustained cultivation and proliferation in vitro. [Methods] Using gene homologous recombination technology, the coding sequences (CDS) of immortalization genes-including human telomerase reverse transcriptase (hTERT), simian virus 40 large T antigen (SV40LT), acute myeloid leukemia fusion genes NUP98-KDM5A (N/K) and CBFA2T3-GLIS2 (C/G), as well as the proto-oncogene KRAS were precisely inserted into the tetracycline (Tet)-inducible eukaryotic expression lentiviral vector pLV2-TRE3GS-EGFP-MCS-3×FLAG-hPGK-Tet-On-SV40-Neo and the transposon PB-TRE3G-3×FLAG-T2A-Puro-SV40-PA. Lentiviral packaging, cell transfection, mRNA expression analysis, Western blotting for protein detection, green fluorescent protein (GFP) visualization, and cell proliferation assays were conducted to evaluate transfection efficiency and assess the regulatory effects of Tet on gene expression in 293T and MEF cells. [Results] The Tet-inducible lentiviral vectors pLV2-Tet-SV40LT, pLV2-Tet-N/K, and pLV2-Tet-C/G, along with the transposon vectors PB-Tet-hTERT, PB-Tet-SV40LT, PB-Tet-N/K, PB-Tet-C/G, and PB-Tet-KRAS, were successfully constructed. In 293T cells, the expression levels of all target genes were upregulated after transfection. In MEF cells, the immortalizing functions of SV40LT and N/K were validated. By modulating Tet addition, cell proliferation levels were effectively regulated, leading to the successful establishment of conditionally immortalized pLV2-SV40LT-MEF and pLV2-N/K-MEF cell lines. [Conclusion] The construction of Tet-inducible immortalizing gene vectors provides a technical foundation for establishing conditionally immortalized primary cell lines, thereby facilitating research on the large-scale in vitro production and expansion of blood cells, such as erythrocytes and platelets.